Implementasi Model Pengajaran Terarah Melalui Kegiatan Membaca Bersama Untuk Meningkatkan Ketrampilan Literasi Mata Pelajaran Bahasa Indonesia - Hatta Hatta (Universtas Negeri Makassar, 2022)
The aim of this research is to improve the learning outcomes of SD Inpres Paccekke Students, Soppeng Riaja Subdistrict, Barru Regency through Guided Teaching Through Joint Reading Activities to Improve Literacy Skills in Indonesian Language Subjects. The research method used is this type of research is classroom action research (CAR), with implementation stages including: (1) planning, (2) implementation, (3) observation and evaluation, (4) reflection. The conclusion in this research is that the Implementation of a Guided Teaching Model through Shared Reading Activities can Improve Literacy Skills in Indonesian Language Subjects. This can be seen from the increase in learning outcomes from cycle I to cycle II.